EDUCAŢIA PERSONALITĂŢII PROACTIVE - USM ADMIN (Moldova State University, 2010)
The principle of pro-activity as the basis of education is examined in the article. The given phenomenon contributes to the changes of personality that take place due to some organizational rules supported by individual experiences. The author emphases four variants of significant manifestation of pupil pro-activity treated both on theoretical and praxio- logical analysis of musical and artistic activity of a pupil.